2022
DOI: 10.37216/tadib.v20i1.536
|View full text |Cite
|
Sign up to set email alerts
|

Eksistensi Seni Kaligrafi Dalam Pendidikan Islam

Abstract: Tujuan penelitian ini ialah untuk mengetahui bagaimana eksistensi seni kaligrafi dalam pendidikan islam. Tujuan dari pendidikan islam ialah terbentuknya peserta didik yang berkepribadian islami sesuai dengan syariat Islam serta memegang teguh tauhid. Dalam penyampaian pembelajaran tentu diperlukan metode yang beragam dan menyenangkan sehingga pembelajaran dapat berjalan dengan baik, mencapai tujuan pendidikan serta peserta didik paham dan tertarik  untuk mengikuti pembelajaran. Pada pembelajaran Pendidikan Aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 3 publications
0
0
0
1
Order By: Relevance
“…Calligraphy art is a beautiful art of the work of human hands related to the field of writing and there is a religious meaning in the writing. (Lestari et al, 2021;Syarofah et al, 2022)..…”
Section: Results and Discussion A Definition Of Calligraphymentioning
confidence: 99%
See 1 more Smart Citation
“…Calligraphy art is a beautiful art of the work of human hands related to the field of writing and there is a religious meaning in the writing. (Lestari et al, 2021;Syarofah et al, 2022)..…”
Section: Results and Discussion A Definition Of Calligraphymentioning
confidence: 99%
“…The learning system is a set of elements that are interconnected and related, and can also contain the way learning is carried out in order to achieve the objectives of the learning. (Syarofah et al, 2022).. It can be concluded that the system in learning is a method or concept that is organized and carried out during the learning process, with the aim of achieving the success of the learning.…”
Section: Calligraphy Learning System At Islamic Boarding School Islam...mentioning
confidence: 99%
“…Dalam bahasa arab, kaligrafi sering disebut dengan khat yang mengandung arti gari atau sebuah tulusan yang indah. Dalam hal ini kaligrafi merupakan ilmu yang berfungsi untuk mengetahui kedudukan huruf dengan ketentuaketentuan tertentu dalam penyusunannya (Syarofah 2022).…”
Section: Nilai-nilai Pendidikan Islam Dalam Seni Kaligrafiunclassified
“…Another opinion was also said by Van Hoeve in Wildan's journal that title SenidalamPerspektif Islam that art is a magnificence that is connected to the human spirit and body so it canbe respond by the five senses and it can be intermediary a communication tool that can be felt (Wildan, 2007). It was suitable with both of the opinions, Ki Hajar Dewantara also said that art is all a person's behavior that is created from magnificence that can be of interest to the society (Syarofah et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…So as with Islam, Islam is a religion that is strongly related to art. Art in Islam itself can be interpreted asaform of presenting magnificence or aesthetics,wherever this art still prioritizes the value of monotheism and faith which unites Allah SWT (Syarofah et al, 2022). The connection between art and Islam is in essence no longer a new thing to know.…”
Section: Introductionmentioning
confidence: 99%